Peer review of the pesticide risk assessment of the active substance folpet - Álvarez, Fernando; Arena, Maria; Auteri, Domenica; Leite, Sofia Batista; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Cioca, Ana‐Andreea; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; et al. (EFSA journal, 2023)
The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Austria and co‐rapporteur Member State Italy for the pesticide active substance folpet and of confirmatory data following the MRL review under Article 12 of Regulation (EC) No 396/2005. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of folpet as a fungicide on barley, wheat and wine grape (field uses) and tomato (field and greenhouse uses). The reliable end points, appropriate for use in regulatory risk assessment and the confirmatory data, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.